Lifetime physical activity and risk of breast cancer in pre-and post-menopausal women - Si, Si; Boyle, T.; Heyworth, J.; Glass, D.; Saunders, C.; Fritschi, Lin (Springer New York LLC, 2015)
© 2015 Springer Science+Business Media New York To investigate the association between different types of physical activity (PA) and breast cancer. A case–control study of breast cancer was conducted in Western Australia from 2009 to 2011, in which 1205 women with breast cancer and 1789 frequency age-matched breast cancer-free control women were recruited. A self-administered questionnaire was used to collect information about lifetime and age-period recreational, household, occupational and transport physical activities. Detailed questions about demographic characteristics, and relevant reproductive, medical and lifestyle factors were also included. Logistic regression and restrictive cubic spline analyses were applied to investigate the association and dose–response relationship between PA and breast cancer risk. Subgroup analysis was performed regarding menopausal status. We found non-linear dose–response associations between PA and risk of breast cancer. Overall, 95–130 MET-hours/week of total lifetime PA was associated with the lowest breast cancer risk. The effects were stronger among post-menopausal women. We also found that the medium amounts of recreational PA (up to 21 MET-hours/week) were associated with lower breast cancer risk among post-menopausal women. Further analysis on the intensity of recreational PA demonstrated different dose–response associations between moderate- and vigorous-intensity recreational PA and breast cancer risk. We found that PA was associated with a reduced risk of breast cancer among post-menopausal women, but not in a linear fashion. Recreational PA of different intensities may have different dose–response associations with risk of breast cancer.